Influence of Chewing and Clenching on Salivary Cortisol Levels as an Indicator of Stress - Yasuaki Tahara, DDS, PhD;1 Kaoru Sakurai, DDS, PhD;2 (Journal of Prosthodontics, 2007)
The purpose of this study was to investigate the effects of chewing and clenching on salivary cortisol levels as an indicator of stress.